A STUDY OF THE PROBLEMS OF ENGLISH SPEAKING SKILLS OF THE FIRST YEAR STUDENTS AT MAHACHULALONGKORNRAJAVIDYALAYA UNIVERSITY - panthito, bundith (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2019)
The objectives of this research were 1) to study the Problems of English Speaking Skills of the first year students, majoring in English (Bilingual Program), Faculty of Humanities at Mahachulalongkornrajavidyalaya University. 2) to purpose the ways to improve English speaking skills for the first year students in the academic year 2016. The study was both qualitative and quantitative methods. The tool used for collecting data was questionnaires. The samplings were comprised 63 first year students. In-depth interview was conducted with 6 lecturers of MCU. The statistics used for analyzing data were Frequency, Mean, Standard Deviation (S.D.), and Percentage (%). The results of the research were as follows 1. The first year students, aged 18-20 years (27%) because of their practicing and aged 30 up years (19%) because of their practicing a little bit in English. were at a moderate high level (3.34%) 2. The first year students, aged 21-30 years can use speaking skills better than other ages comprising 54% were at a high level of (3.50%) Mean. 3. Students were very satisfied with the improvement of English speaking skills in daily conversation through practicing English speaking skills by watching BBC, CNN news. Self-confidence can also help speaking 3.57% were at the high level. Suggestions for the further study of the problems of English speaking skills of the first year students are: 1) students should be constantly speak English through public speaking especially to learn and understand using face to face communication as well as knowing more extensively vocabulary. 2) Enhancement in applying English sentence structures for interaction between people, so that students are able to improve their confidence in speaking English correctly and completely.